Farmers: beneficiaries or partners ? - Seck, Ibrahim (Technical Centre for Agricultural and Rural Cooperation, 1994)
Ibrahim Seck is President of the Savings and Credit Commission of the Federation of NGOs of Senegal, and is a farmer from Diogo in the Niayes area. What can we say about the state of agricultural development in Africa today? Despite the efforts of...